Comparison of different lipid extraction procedures applied to three microalgal species - M. Gorgich; T. M. Mata; A. A. Martins; M. Branco-Vieira; N. S. Caetano (Energy Reports, 2020)
The increase in the world's energy demand has contributed to the emergence of new sustainable energy sources, such as microalgae, with their great potential to provide biofuels and other high value co-products for the food and health's markets. However, current biorefinery methodologies are either too complex to extract the targeted components such as high-value products, or require solvents with toxicity for humans and the environment. This work aims to evaluate different lipid extraction approaches applied to three microalgal species: Chlorella zofingiensis, Phaeodactylum tricornutum, and Arthrospira platensis, while employing less toxic and more economical solvents for the lipids extraction. Experimental results showed a promising outcome to tune current biorefinery methodologies, enhancing product yield as well as decreasing potential hazards.
Keywords: 330; Biodiesel; Microalgae; Biorefinery; Lipid extraction